Precise Structural Regulation and Band-Gap Engineering of Curved Graphene Nanoribbons - Niu, Wenhui; Ma, Ji; Feng, Xinliang (Accounts of Chemical Research, 2022)
ConspectusGraphene nanoribbons (GNRs)─quasi-one-dimensional graphene cutouts─have drawn growing attention as promising candidates for next-generation electronic and spintronic materials. Theoretical and experimental studies have demonstrated that the electronic and magnetic properties of GNRs critically depend on their widths and edge topologies. Thus, the preparation of structurally defined GNRs is highly desirable not only for their fundamental physicochemical studies but also for their future technological development in carbon-based nanoelectronics. In the past decade, significant efforts have been made to construct a wide variety of GNRs with well-defined widths and edge structures via bottom-up synthesis. In addition to extensively studied planar GNRs consisting of armchair, zigzag, or gulf edges, curved GNRs (cGNRs) bearing cove ([4]helicene unit) or fjord ([5]helicene unit) regions along the ribbon edges have received increasing interest after we presented the first attempt to synthesize the fully cove-edged GNRs in 2015. Profiting from their novel edge topologies, cGNRs usually exhibit an unprecedented narrow band gap and high carrier transport mobility in comparison to the planar GNRs with similar widths. Moreover, cGNRs with particular out-of-plane-distorted structures are expected to provide further opportunities in nonlinear optics and asymmetric catalysis. However, the synthesis of cGNRs bearing cove or fjord edges remains underdeveloped due to the absence of efficient synthetic strategies/methods and suitable molecular precursor design.In this Account, we present the recent advances in the bottom-up synthesis and characterization of structurally defined cGNRs containing cove or fjord edges, mainly from our research group. First, the synthetic strategies toward cGNRs bearing cove edges are described, including the design of molecular monomers and polymer precursors as well as the corresponding polymerization methods, such as Ullmann coupling, Yamamoto coupling, A2B2-type Diels-Alder polymerization, followed by Scholl-type cyclodehydrogenation. The synthesis of typical model compounds is also described to support the understanding of the related cGNRs. In addition, the synthesis of cGNRs containing fjord edges from other research groups via the regioselective Scholl reaction, Hopf cyclization or regioselective photochemical cyclodehydrochlorination approach is presented. Second, we discuss the optoelectronic properties of the as-synthesized cGNRs and reveal the design principle to obtain cGNRs with high charge carrier mobilities. Finally, the challenges and prospects in the design and synthesis of cGNRs are offered. We anticipate that this Account will further stimulate the development of cGNRs through a collaborative effort between different disciplines.
CRIS-Team Scopus Importer:2023-03-20